Particulate matter emission during municipal solid waste combustion: Submicron particulates formation mechanism. (15th February 2022) - Yang, Wu; Pudasainee, Deepak; Gupta, Rajender; Li, Wei; Wang, Ben; Sun, Lushi
Graphical abstract: Highlights: PM0.2 and PM0.2-1 yields showed opposite trends with combustion temperature increase. NaCl, KCl, K3 Na(SO4 )2, and SiO2 are the major inorganic mineral components in PM1 . The "crystallization" modes formed by alkali chlorides was found in PM0.2-1. The heterogeneous nucleation of alkali chloride and sulfate promote PM0.2-1 formation. Abstract: This paper presents an information on size distribution, inorganic composition and formation mechanism of submicron particles generated from MSW combustion. The XRD and CCSEM analysis results clearly showed that NaCl, KCl, K3 Na(SO4 )2, and SiO2 are the major inorganic mineral components in submicron particles. Submicron particles are mainly composed of organic components, alkali chlorides, alkali sulfates, and refractory inorganic minerals, but they account for different proportions in PM0.2 and PM0.2-1 . There are five formation modes of submicron particles in MSW combustion: "condensation", "nucleation", "accumulation", "crystallization" and "fragmentation". The "condensation" mechanism mainly seen in PM0.2 composed of gas components, the "crystallization" and "fragmentation" modes formed by alkali salts and char particles are mainly present in PM0.2-1, the "nucleation" and "accumulation" modes coexist in PM0.2 and PM0.2-1 . As the combustion temperature increased, the alkali chlorides and sulfates in the "crystallization" form decreased, and the inorganic mineral components in the "nucleation" form increased, which results in the variation of size distribution of submicron particles. In addition, volatile alkali salt nucleation experiments show that when alkali chloride and sulfate coexist in high-temperature flue gas, heterogeneous nucleation and agglomeration can significantly enhance the accumulation of particles in the range of 0.2–0.5 μm.